Solve the system of equations: $$\begin{cases}\dfrac{x^2+xy+y^2}{x^2+y^2+1}=\dfrac{1}{xy} \\\left(\sqrt{3}+xy\right)^{\log_2x}+\dfrac{x}{\left(\sqrt{3}-xy\right)^{\log_2y}}= 1+\dfrac{x}{y}\end{cases}$$

My try: $\dfrac{x^2+xy+y^2}{x^2+y^2+1}=\dfrac{1}{xy}\\\Leftrightarrow xy\left(x^2+y^2\right)+\left(xy\right)^2= x^2+y^2+1\\\Leftrightarrow\left(xy-1\right)\left(x^2+y^2+xy+1\right)=0\\\Leftrightarrow xy=1\,\,\,\mbox{(because:}\,\, x^2+y^2+xy+1>0)$

And here I'm stuck!

  • $\begingroup$ if i answered your question then please mark it so! $\endgroup$ – PleaseHelp Nov 10 '13 at 6:33

Subsitute $xy=1 , y=1/x,and \, log y=-logx$ :-

$log(3^{1/2}+1)^{logx}+ x*log(3^{1/2}-1)^{logx}=1+x^2$

then take Log at both sides of your equation then your 2nd equation becomes

$logx*log(3^{1/2}+1)+logx+ logx*log(3^{1/2}-1)=2logx$

$log(3^{1/2}+1)+ log(3^{1/2}-1)=1$


which is always true!

  • $\begingroup$ of course i have leap frogged some steps. $\endgroup$ – PleaseHelp Nov 9 '13 at 17:45

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.